UPAYA GURU PAI DALAM MENGATASI KENAKALAN REMAJA DI SMK AL-KAUTSAR JOMBANG - Fianti Nono; Beny Sintasari (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
Juvenile delinquency is a very serious problem, so it must be addressed immediately so that it does not turn into a crime. Teenagers must be trained by instilling Islamic religious education. Through a religious personality, it is possible for teenagers not to commit delinquency or violations so that the lives of teenagers or those around them become calm and peaceful without any disturbance. The purpose of this research is 1. To describe juvenile delinquency in Al-Kautsar Diwek Jombang. 2. To describe the efforts of Islamic Religious Education teachers at SMK Al-Kautsar Diwek Jombang in overcoming juvenile delinquency. The method used in this study is a qualitative method with a qualitative descriptive research design using data collection techniques, namely observation, interviews, and documentation. The results showed that the forms of juvenile delinquency at Al-Kautsar Vocational High School, Diwek Jombang included: being late, skipping class, arguing with the teacher, wearing clothes that were not in accordance with the rules, but more often than not, being late and skipping. Some of the causative factors are from within the adolescent due to a lack of sense of responsibility, and external factors such as the family, community/school environment, and technology/mass media. The efforts or efforts made by PAI teachers or the school are divided into three; 1. Preventive such as by making the Duha prayer a habit before entering class, giving appeals after the Duha prayer, being exemplary, adding religious class hours, and supervision ( CC TV and manual and digital absences 2. Curative efforts such as giving sanctions or punishments for teenagers who commit delinquency, placing adolescents in activities that these adolescents are capable of, 3. Development efforts such as giving advice, making approaches, and counseling.